A Spanish Survey on the Perioperative Use of Antimicrobials in Small Animals - Otero Balda, Ignacio; Fuertes Recuero, Manuel; Penelo Hidalgo, Silvia; Espinel Rupérez, Jorge; Lapostolle, Benoit; Ayllon Santiago, Tania; Ortiz Díez, Gustavo (My University, 2023)
Appropriate use of perioperative antimicrobials can significantly reduce the risk of postoperative infections. However, inappropriate antimicrobial use can result in the creation of multidrugresistant bacteria, increased costs, host flora disruption, side effects and increased risk of hospitalacquired infections. This survey evaluated the current perioperative use of antimicrobials in small animals by Spanish veterinarians using a web-based questionnaire. Responses were represented using descriptive statistics and a statistical analysis of the association between demographic data and perioperative antimicrobial use was performed. Pre-operative antimicrobials were administered in clean surgery by up to 68.3% of participants, 81.0% in clean-contaminated surgery and 71.3% in dirty surgery, while in the post-operative period, antimicrobials were administered by up to 86.3% of participants in clean surgery, 93.2% in clean-contaminated surgery and 87.5% in dirty surgery. Factors considered ¿very important¿ for antimicrobial selection were the degree of wound contamination, patient immunosuppression and use of prosthesis. The most frequently used antimicrobial was beta-lactamase-resistant (or potentiated) penicillin. Post-operative antimicrobial use was associated with participants without specific surgical postgraduate training. This study highlights an overuse of antimicrobials in perioperative procedures in small animal surgery in Spain. Therefore, evidence-based guidelines and further education regarding the correct use of antimicrobial prophylaxis are recommended
Keywords: nosocomial infections; questionnaire; veterinarians; small animals; antimicrobial use